ORGANISING TOURISM PROVIDERS ON REMOTE TOURING TRACKS AS GEOGRAPHICALLY DISPERSED TEAMS - Cartan, Greg; Carson, Dean (The journal of contemporary issues in business and government, 2011)
The Australian outback is a popular tourism destination. Iconic four wheel drive touring tracks are particularly attractive. This study considers how tourism providers are organised in remote touring tracks (RTTs) through a case study of the Oodnadatta Track. A framework developed from the geographically dispersed teams’ (GDTs) literature provided the analytical lens for the study. This framework produced a useful description and explanation of the contemporary context and also a tentative improvement agenda. Particularly noteworthy was the question of leadership, which emerged as an influential and pervasive factor.